Pengendalian Persediaan Bahan Baku Dengan Metode Material Requirement Planning Pada Produksi Majalah SM PT ABC - Alvita, Alvita Alifdiyani; Widya, Widya Setiafindari (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2024)
PT ABC operates in the printing and publishing sector which produces magazines using a make to order system. The problem that often occurs is related to the fluctuating demand for SM magazines from March 2021 to February 2024. As a result of this condition, the company cannot estimate the amount of raw materials needed, so orders are made based on estimates only. This causes overstock, especially 1001 reams of 58 gram HVS paper. The research objective is to find out planning, inventory control, and ordering techniques that produce minimal costs. In this case, suitable methods to apply are Material Requirement Planning (MRP), lot size Economic Order Quantity (EOQ), Lot For Lot (LFL) and Period Order Quantity (POQ). From the proposed improvements, the minimum cost with Lot For Lot (LFL) was IDR 2.320.000. So, costs can be minimized to IDR 93.260.746 or 98% compared to the method used by the company.